Thermal Conductivity of Micro Steel Fiber Reinforced Concrete - Zainal Abidin, Mohd Fitri; Mohd Zuki, Sharifah Salwa (Recent Trends in Civil Engineering and Built Environment, 2021)
Malaysia was a tropical country where it’s hot and humid all year round. A fiber concrete wall was needed to maintain the building occupants’ indoor environment comfort due to high temperature. There is a demand to improve energy efficiency through passive design and thermal insulation of building envelopes using micro steel fibers. This study utilized micro steel fiber in concrete construction. The objective was to determine the thermal conductivity of micro steel fiber concrete and evaluate the relationship between concrete density and porosity. Micro steel fibers used as an admixture with different percentages from 0.5%, 0.75%, 1.0%, and 1.25% by weight were used for concrete with 100mm length, 100mm width, and 100mm height. The concrete grade for the specimen is grade 40. The slump test was conducted to determine the properties of micro steel and the workability of concrete. Furthermore, the samples were examined by using Hot Guarded Box to obtain the constant difference temperature. After 28 days of curing, all concrete samples were tested to find density, water absorption, and thermal conductivity value and developed a relationship between the parameters. After that, the concrete has been tested with thermal conductivity. The result shows that micro steel fiber concrete’s thermal conductivity increased moderately with the increase of micro steel fiber percentage. The percentage of water absorption of micro steel fiber concrete decreased when the density of concrete increased. Lastly, micro steel fiber uses thermal insulation material less suitable for concreting in the hot environment, such as Malaysia, as it gives higher thermal value than normal concrete.